1876 Ala. Code 901, § 4230 - (:unkn) unknown (My University, 1876)
§ 4230: "Any person who sells, gives, or lends, to any boy under eighteen years of age, any pistol, or bowie knife, or other knife of like kind or description, must, on conviction, be fined not less than fifty, nor more than five hundred dollars."
Keywords: TRANSFER - MINORS